TRANSFORMASI JURU BICARA PUBLIC RELATIONS DI ERA ARTIFICIAL INTELLIGENCE - Bilal Bilal (Sintesa, 2026)
The development of Artificial Intelligence (AI) has transformed Public Relations practices, particularly in organizational crisis communication. This study aims to analyze the changing role of organizational spokespersons in the AI era, the use of AI in crisis communication, and its implications for communication credibility. This research employs a qualitative literature review by analyzing journals and relevant literature published between 2020 and 2025. The findings reveal that AI enhances communication effectiveness through data analysis, issue monitoring, and automated information delivery. However, AI cannot fully replace human spokespersons due to limitations in empathy, credibility, and ethical judgment. Therefore, collaboration between humans and technology emerges as the most relevant model for organizational communication in the era of artificial intelligence. Keywords: Artificial Intelligence, Public Relations, Spokesperson, Crisis Communication.